(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The purpose of this study is discuss the effect of Corporate Governance in the Tax Planning, has been made in a sample of Iraqi Industrial contribution Companies listed in Iraqi Stock Exchange Market (ISE) , for the period from 2008 to 2012.The study used the" Experimental Research Approach" . Also used the (Modified Jones Model, 1995) in order to measure the corporate governance, to measure the extent of the practice of corporate governance in the samples companies. While it use to measure tax planning, the model that used by studies and researches of tax that adopted in discussions of tax reform, by analyzing the financial statements of companies to reach a measurement for the two variables of the study. The study results indicate that there was no significant effect of corporate governance in tax planning. The most important conclusion that study found: That the intersection that may caused by corporate governance in tax rules not due to deficiencies afflict the corporate governance systems, but due to tax rules proceed from the premise of "public interest" while the principles and rules of corporate governance proceed from, "the premise of public interest and shareholders’ interests " so the problem of incompatibility between them has emerged because of the difference and conflict of interests. The study also found that Iraqi companies a sample of Research are arise to tax planning practice according to the results of the analysis of financial statements of these companies. And also found that the choice of the company to its tax strategy to be based on personal objectives of the management, regardless whether those objectives are compatible or incompatible with the objectives of the Tax Administration and the objectives of the society, according to the principle of maximizing the benefits of each side to own at the expense of other sides.